PUSAT KURSUS BAHASA INGGRIS BANJARBARU - Pribadi, Faiz Baihaqi; Tharziansyah, Muhammad (UNIVERSITAS LAMBUNG MANGKURAT, 2022)
English Course Center Banjarbaru aims to make the place a gathering center for activities to introduce or show the importance of speaking English in life for the general public, where there is a lot of potential that requires foreign language skills, especially English. Even so, Banjarbaru as an education city still does not have it, due to the lack of public interest in English. Therefore, the Banjarbaru English Course Center was designed, using the concept of character and the metaphorical method, which is expected to create an English course center that represents the identity of the country of origin and is translated into architectural visuals. The character concept, which takes the English variable and uses a landmark metaphorical approach in England, was chosen because it is able to represent the English Course Center.